Implementasi Peran Polisi Militer TNI AL di Kri Untuk Mendukung Tugas Pokok TNI Angkatan Laut di Puspomal - Tony Soelarso Herry Soetjipto; Hendrik Kurniawan; Hanla Hanla; Dani Wira Nugraha (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study discusses the role of the Indonesian Navy Military Police (Pomal) aboard warships (KRI) in supporting the core tasks of the Indonesian Navy, particularly in maintaining discipline, enforcing the law, and upholding military order among personnel. Pomal serves as the law enforcer on board the KRI, ensuring that all personnel comply with the regulations in place. The study finds that despite the crucial role of Pomal, it faces various challenges, such as limited human resources, inadequate law enforcement facilities, and overlapping authority with the ship's command structure. Furthermore, the geographical challenges, which separate the KRI from naval bases or other military legal authorities, affect the effectiveness of law enforcement. Nonetheless, Pomal strives to overcome these challenges by optimizing coordination between Pomal personnel and the KRI Commander. This research recommends the improvement of supporting facilities, clearer authority structures, and enhanced coordination between relevant parties to improve the effectiveness of law enforcement and discipline enforcement on KRI.